Changes in minimum temperatures in Europe - Žiberna, Igor; Meško, Matej (Journal for Geography, 2021)
Changes in minimum temperatures in Europe In article, we analyse trends of minimum temperatures in Europe between 1961 and 2020 and changes in minimum temperatures until the end of the 21st century. The analysis uses data for 58 meteorological stations with a homogeneous dataset, minimum temperature data from the WorldClim database and minimum temperature projections to the end of the 21st century from the WorldClim database. The results show large differences in seasonal and spatial variations of minimum temperatures.